2006
DOI: 10.1161/01.atv.0000229659.94020.53
|View full text |Cite
|
Sign up to set email alerts
|

Parthenolide Modulates the NF-κB–Mediated Inflammatory Responses in Experimental Atherosclerosis

Abstract: NF-kappaB inhibition by PTN retards atherosclerotic lesions in apoE mice, by reducing lesion size and changing plaque composition. This natural compound could represent a novel therapeutic approach to inflammation during vascular damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
79
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 49 publications
6
79
0
1
Order By: Relevance
“…By Western blots, we observed that 10% FBS induced IκBα  degradation, which may be related to the activation of NF-κB signal pathway and the proliferation of VSMCs stimulated by enriched serum. However, the presence of parthenolide completely antagonized this effect and resulted in upregulation of IκBα protein, which is in agreement with the previous reports showing parthenolide as an inhibitor of NF-κB Sheehan et al, 2002;Hehner et al, 1998;López-Franco et al, 2006). As an inducible isoform of enzyme, Cox-2 is upregulated in response to inflammatory factors and some peptides (Bishop-Bailey et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…By Western blots, we observed that 10% FBS induced IκBα  degradation, which may be related to the activation of NF-κB signal pathway and the proliferation of VSMCs stimulated by enriched serum. However, the presence of parthenolide completely antagonized this effect and resulted in upregulation of IκBα protein, which is in agreement with the previous reports showing parthenolide as an inhibitor of NF-κB Sheehan et al, 2002;Hehner et al, 1998;López-Franco et al, 2006). As an inducible isoform of enzyme, Cox-2 is upregulated in response to inflammatory factors and some peptides (Bishop-Bailey et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…IκBα is the specific cytoplasmic inhibitory protein of NF-κB, and degradation of IκBα is generally believed to be the critical step for the activation of NF-κB (Brown et al, 1993). A recent study indicated that in vascular smooth muscle cells and monocytes stimulated with lipopolysaccharide (LPS), parthenolide reduced IκBα degradation and NF-κB activation (López-Franco et al, 2006). By Western blots, we observed that 10% FBS induced IκBα  degradation, which may be related to the activation of NF-κB signal pathway and the proliferation of VSMCs stimulated by enriched serum.…”
Section: Discussionmentioning
confidence: 99%
“…Lesional macrophages (MOMA-2; AbD Serotec, Oxford, U.K.), CD3 T cells, vascular smooth muscle cells (VSMCs) (a-actin-Cy3; Sigma-Aldrich), chemokine (C-C motif) ligand (CCL) 2 (Santa Cruz Biotechnology), CCL5 (Antibodies Online), and tumor necrosis factor a (TNF-a; Santa Cruz Biotechnology) were detected by immunoperoxidase or immunofluorescence. Positive staining was expressed as percentage of total plaque area or number of positive cells per lesion area (26,27). Activated NF-kB in kidney and aorta was detected by Southwestern histochemistry using digoxigenin-labeled probes (26,28 (23).…”
Section: Histological Analysismentioning
confidence: 99%
“…Positive staining was expressed as percentage of total plaque area or number of positive cells per lesion area (26,27). Activated NF-kB in kidney and aorta was detected by Southwestern histochemistry using digoxigenin-labeled probes (26,28 (23). Murine monocyte/macrophage cell line (RAW 264.7, TIB-71; ATCC) was maintained in DMEM with 10% FBS.…”
Section: Histological Analysismentioning
confidence: 99%
“…Estudos anteriores já estabeleceram que a expansão do tecido adiposo, tal como observado na obesidade, está associada a uma resposta inflamatória crônica e em resistência à insulina (123). Recentemente estudos têm implicado o tecido adiposo no processo inflamatório, demonstrando que os adipócitos maduros e pré-adipócitos de origem murina expressam múltiplos TLRs desde TLR1 a TLR9 (124)(125)(126).…”
Section: Discussionunclassified